Enhancement of the helical twisting power with increasing the terminal chain length of nonchiral bent-core molecules doped in a chiral nematic liquid crystal. Issue 4 (12th January 2017) - Jo, Seong-Yong; Kim, Byeong-Cheon; Jeon, Sung-Wook; Bae, Jae-Hyun; Walker, Martin; Wilson, Mark; Choi, Suk-Won; Takezoe, Hideo
Abstract : We measured the helical twisting power (HTP) of nonchiral bent-core molecules doped in a chiral nematic liquid crystal, and found that HTP increases with the terminal chain length. Abstract : In this work, we prepared a series of nonchiral bent-core molecules with different terminal alkoxy chain lengths, and measured the helical twisting power (HTP) of the bent-core molecules doped in a chiral nematic liquid crystal (N*LC). We investigated the doping effect through the colour change and spectral change due to the Bragg (selective) reflection and found that the bent-core molecules with longer alkoxy chains showed stronger HTP under chiral circumstances such as N*LC. Namely, not only the axial conformations at wings linked to the bent central unit but also the length of the alkoxy chains at the terminal positions of the bent-core molecules play an important role in the resulting unusual chiral behaviour. A preliminary stochastic dynamics simulation to determine the distribution of the chirality order parameters was made, being consistent with the present experimental result.